THE Creating Value Innovation With Blue Ocean Strategy at “A Leather Bags” - Ajoe Kartika Mastaka; Dewi Kartikaningsih (Dinasti Publisher, 2024)
“A LEATHER BAGS” a company that manufactures leather bags made from cow leather. The number of similar leather bag business causes high competition. Therefore, strategies that provide more value to consumers are needed. This study aimed to find out the right strategy to be applied by “A Leather Bags” to design a strategy that focuses on creating new market space through a canvas strategy analysis and a four-step framework through the value innovation process. A strategy canvas sanalysis was used to determine the company’s position against competitors in the market. A four-step framework is used to determine what factors need to be eliminated, reduced, improved and which will be created by the Blue Ocean strategy. This research was conducted by distributing questionnaires, which the samples were 36 leather bag community members in Solo. The results of the research and discussion, the strategy that needs to be applied “A Leather Bags” Indonesia was to renew the purchasing procedure in which previously on every order of product colors and different skin types into the same color and skin type, product innovation by increasing the quality of raw material products to increase the superiority of product compared that previous product, and the last, to open services for product maintenance services and repair “A Leather Bags” products that have been purchased by consumers.